2008
DOI: 10.1111/j.1532-950x.2008.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biomechanical Comparison of Locking Compression Plate Fixation and Limited‐Contact Dynamic Compression Plate Fixation of Osteotomized Equine Third Metacarpal Bones

Abstract: The results of this in vitro study may provide information to aid in the selection of a biological plate for the repair of equine long bone fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 8 publications
1
47
2
2
Order By: Relevance
“…Interestingly, the replacement of a single nonlocking screw with a locking screw increased the torque to failure by 17% . Similarly, hybrid plating in equine ex vivo studies has shown biomechanical superiority to all nonlocking constructs which included the limited contact DCP (LC‐DCP) …”
mentioning
confidence: 99%
“…Interestingly, the replacement of a single nonlocking screw with a locking screw increased the torque to failure by 17% . Similarly, hybrid plating in equine ex vivo studies has shown biomechanical superiority to all nonlocking constructs which included the limited contact DCP (LC‐DCP) …”
mentioning
confidence: 99%
“…LCPs have been increasingly used in horses. [10][11][12][13] Compared with conventional plates, LCPs rely on completely different mechanical principles to …”
Section: Discussionmentioning
confidence: 99%
“…Das Akronym "PC-FIX" steht für "Point-Contact Fixateur", was eine Weiterentwicklung der LC-DCP darstellt und als eigentlicher "Fixateur Interne" angesehen werden kann (Tepic und Perren 1995 Zahlreiche In vitro-Studien konnten die Überlegenheit der Verriegelungssysteme über die früheren Frakturfixationstechniken beweisen (Sod et al 2008a, 2008b, Ahern et al 2013 (Bramlage 1999, Fürst 2012 …”
Section: Pc-fixunclassified